Job security: a legal duty to consult or negotiate? - Yawa, Elias Mzwanele (Department of Commercial Law, 2021)
This dissertation investigates whether or not there is a duty on the employer to negotiate with workers on issues that affect their employment security. The research focuses on why there is no duty on the employer to negotiate with workers in regard to retrenchment, closure and transfer of undertakings. It also examines the--factors that are obstacles to the existence of such a duty. Furthermore, the effects of ·such _non - negotiation on the workers' job security and on efficiency as well as productivity of the undertaking are looked at. It also evaluates whether the results suggest that unilateralism in these respects is making a useful contribution to the realisation of the principal aim of ,the LRA -industrial peace. The method of investigation has largely been literature review and to a certain extent / comparative. It analyses primary and secondary sources. Theoretical guidance was drawn from critical studies in labour law and industrial relations. The study reveals that there is no duty on the employer to negotiate with workers regarding retrenchment, closure and transfer of undertakings. Consequently, it argues that, for job security to ensue, industrial peace to prevail, business efficiently and productivity to abound, the employer should be compelled to bargain or negotiate with workers. This duty should be clearly stipulated in legislation. It further argues that consultation should be geared towards agreement. If agreement cannot be reached on the issues under consideration, it argues that the status quo should be maintained, that is no change to existing conditions should be implemented until a deadlock- breaking mechanism resolves the matter. The aim of the work is threefold. First, it seeks to make a modest contribution to the understanding and importance of the duty to negotiate in labour law and industrial relations · for post -Apartheid south Africa. Second, it disputes and, in large measure, seeks to contradict earlier justifications for refusing to compel the employer to negotiate with workers in regard to retrenchment, closure and transfer of undertakings. Third, it attempts to provide insight into how this duty can best be rendered more meaningful and equally beneficial to workers and employers. Turning to the assessment, it finds that the insistence on duty to consult as opposed to duty to negotiate is pro -management and that it dangerously puts our labour relations into the horns of a dilemma. Furthermore, such an approach is out of touch with democratic developments in the country as well as the expectations of the industrial relations community. Lastly, it finds that the duty to consult is not as useful as the one to negotiate. It accordingly proposes that the employer be under a legislative obligation to negotiate and reach consensus with workers on issues affecting job security.